Preventive Leptin Administration Protects Against Sepsis Through Improving Hypotension, Tachycardia, Oxidative Stress Burst, Multiple Organ Dysfunction, and Increasing Survival - Vallejos, Alejandro; Olivares, Pedro; Varela, Diego; Echeverria, Cesar; Cabello-Verrugio, Claudio; Pérez-Leighton, Claudio; Simon, Felipe (Frontiers in Physiology, 2018)
Sepsis syndrome is the most important cause of mortality in critically ill patients admitted to intensive care units (ICU). However, current therapies for its prevention and treatment are still unsatisfactory, and the mortality rate is still high. Non-septic ICU patients are vulnerable to acquire sepsis syndrome. Thus, a preventive treatment for this population is needed. During sepsis syndrome and endotoxemia, severe hypotension, tachycardia, oxidative and immune response increase, multiple organ dysfunction syndrome (MODS) and decreased survival are observed. Leptin administration protects against negative effects of sepsis syndrome and endotoxemia. Furthermore, it is has been reported that leptin elevates blood pressure mediated by sympathetic nervous system activation. However, whether leptin mediates its protective effects during sepsis through blood pressure regulation is not known. Therefore, we investigate whether leptin improves blood pressure and MODS, resulting in survival increase during endotoxemia. The results showed that leptin treatment reduced both the hypotension and tachycardia characteristically observed during endotoxemia. Notably, this protective effect was observed early and late in the course of endotoxemia. Endotoxemia-induced MODS decreased in leptin-treated rats, which was reflected in normal values for liver and kidney function, inhibition of muscle mass wasting and maintenance of glycemia. Furthermore, leptin treatment decreased the oxidative stress burst in blood and blunted the increased pro-inflammatory cytokines TNF-α, IL-1β and IL-6 observed during endotoxemia. Remarkably, according to the leptin-induced increase in survival, leptin administration decreased the risk for death associated with sepsis syndrome at early and late times after endotoxemia induction. These results show a potential preventive therapy against sepsis syndrome and endotoxemia in vulnerable patients, based in the beneficial actions of leptin.